SUSTAINABILITY FROM CONCEPT TO PARADIGM OF ENVIRONMENTAL POLICIES - Adela Sorinela SAFTA; Lavinia POPESCU (Eastern European Journal of Regional Studies, 2024)
This paper analyzes by transposing the importance of environmental policies, highlighting the most significant regulations directly related to the sustainable agriculture component in relation to the environmental targets proposed by the Municipal Agricultural Policy. The need to rethink agricultural processes led slowly to the anchoring to current trends as a premise in the realization of a real report related to sustainable agricultural systems performing and last but not least aligned to the constraints of eco-conditionality. From this perspective, the methodology in reflecting our analysis was linked to the collection of data reported in international statistical databases such as those available at the National Institute of Statistics Eurostat, as well as OECD reports on the subjects analyzed in the study. In these paradises, the perspective reflected by the New Agricultural Policy is rather aligned towards the achievement of environmental goals in agriculture, which positions the ability of farmers to adapt to these sustainability conditions. Through these completely new concepts for farmers, the studio reflects the sustainability of agriculture through the levers offered by the agricultural policy and research, thus also representing an important resource in complex research aimed at the decarbonization of agriculture as topical issues.